Analysis of the properties of a coaxial microwave sensor. Features of research of two-layer biological objects - Лю, Чан; Бондаренко, И.Н.; Деревянко, А.А.; Панченко, А.Ю. (Radiotekhnika, 2019)
Sensors based on the use of the near field of electrodynamic systems allow us to determine the properties of objects in a wide range of frequencies. They make it possible getting high resolution. The paper analyzes the resolution of the microwave sensor, for which a rigorous analytical model was created. The analysis is based on solving the problem of describing fields in the working area of such a sensor. The presented mathematical model allows the possibility of expanding the solution to the case of the study of multilayer objects. The preliminary results of calculations of the components of the electromagnetic field in the working area of the sensor are discussed, and its dimensions are estimated.